The shocking story of electricity - Claybourne, Anna. (London : c)
"Not so long ago there were no electrical inventions at all. No computers, no televisions... not even any light bulbs. Here you can read the fascinating story of electricity from the very beginning, when people first realized what electricity was -- and just what it could do." -- Back cover.
Keywords: x; Science -- Juvenile literature. -- History; Electricity -- History